Prevalence of periodontitis in the Indian population: A literature review - Jacob P Shaju; R M Zade; Manas Das (Wolters Kluwer Medknow Publications, 2011)
Background: Periodontitis is one of the major reasons for tooth loss in adults. India, with a population of over 1 billion, is bound to become a developed nation soon. This transition will require a population that is healthy, including in terms of periodontal health. Early studies done in India gave an indication that the population is highly susceptible to periodontitis. Aim: This paper reviews the prevalence of periodontitis in the Indian population. Settings and Design: Review of periodontitis prevalence studies on the Indian population. Materials and Methods: After identifying articles from PubMed and hand searching, the epidemiology of periodontitis is reviewed together with the case definition, study settings, type of population, age and other factors as all these are bound to affect the prevalence rates determined in various studies. Statistical Analysis: None. Results: This review identifies very limited number of studies that provide prevalence data and faces difficulty in comparing various studies due to nonstandardization of case definition and use of nonrepresentative samples. There is a high prevalence of periodontitis among the adults and the economically weak population. Conclusions: There is a very urgent need for standardized population-based studies with a robust design to identify the true prevalence of periodontitis, which in turn will help in planning oral health policies and creating the necessary infrastructure.